Hydrogen Sulfide Downregulates Oncostatin M Expression via PI3K/Akt/NF-κB Signaling Processes in Neutrophil-like Differentiated HL-60 Cells - Na-Ra Han; Seong-Gyu Ko; Hi-Joon Park; Phil-Dong Moon (MDPI AG, 2023)
The cytokine oncostatin M (OSM) is regarded as a critical mediator in various inflammatory responses. While the gaseous signaling molecule hydrogen sulfide (H2S) plays a role in a variety of pathophysiological conditions, such as hypertension, inflammatory pain, osteoarthritis, ischemic stroke, oxidative stress, retinal degeneration, and inflammatory responses, the underlying mechanism of H2S action on OSM expression in neutrophils needs to be clarified. In this work, we studied how H2S reduces OSM expression in neutrophil-like differentiated (d)HL-60 cells. To evaluate the effects of H2S, sodium hydrosulfide (NaHS, a donor that produces H2S), ELISA, real-time PCR (qPCR), immunoblotting, and immunofluorescence staining were utilized. Although exposure to granulocyte-macrophage colony-stimulating factor (GM-CSF) resulted in upregulated levels of production and mRNA expression of OSM, these upregulated levels were reduced by pretreatment with NaHS in dHL-60 cells. Similarly, the same pretreatment lowered phosphorylated levels of phosphatidylinositol 3-kinase, Akt, and nuclear factor-kB that had been elevated by stimulation with GM-CSF. Overall, our results indicated that H2S could be a therapeutic agent for inflammatory disorders via suppression of OSM.